2016
DOI: 10.1016/j.tox.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of divalent metal toxicity in affective disorders

Abstract: Metals are required for proper brain development and play an important role in a number of neurobiological functions. The Divalent Metal Transporter 1 (DMT1) is a major metal transporter involved in the absorption and metabolism of several essential metals like iron and manganese. However, non-essential divalent metals are also transported through this transporter. Therefore, altered expression of DMT1 can modify the absorption of toxic metals and metal-induced toxicity. An accumulating body of evidence has su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 288 publications
(272 reference statements)
0
25
0
Order By: Relevance
“…The localization of SLC30A10 to the bile duct epithelium in human liver (19) and to the apical domain of polarized HepG2 cells (25) suggests that SLC30A10 is required for Mn export into bile. As for cellular Mn uptake, the plasma membrane protein divalent metal-ion transporter-1 (DMT1) is frequently cited as the primary Mn 2+ importer (26)(27)(28). Although DMT1 can certainly transport Mn (29), a study of intestine-specific DMT1-null mice demonstrated that it is dispensable for Mn absorption (30).…”
mentioning
confidence: 99%
“…The localization of SLC30A10 to the bile duct epithelium in human liver (19) and to the apical domain of polarized HepG2 cells (25) suggests that SLC30A10 is required for Mn export into bile. As for cellular Mn uptake, the plasma membrane protein divalent metal-ion transporter-1 (DMT1) is frequently cited as the primary Mn 2+ importer (26)(27)(28). Although DMT1 can certainly transport Mn (29), a study of intestine-specific DMT1-null mice demonstrated that it is dispensable for Mn absorption (30).…”
mentioning
confidence: 99%
“…Furthermore, the cytotoxicity of soluble metals resulting from intracellular dissolution of metal NPs should be rigorously examined. Numerous studies have demonstrated biochemical alterations and behavioural dysfunction in animals and humans caused by exposure to various metals (Chang et al, 2014;Kim, 2015a, 2015b;Menon et al, 2016). Measuring the soluble metal concentrations of NP-exposed cells and cell culture media would provide important information about the potential effect of NP dissolution on metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…; Han and Kim ; Menon et al . ). For example, iron deficiency in children causes increased anxiety and depression along with social and attention problems (Lozoff et al .…”
mentioning
confidence: 97%
“…Iron plays an established role in proper brain function and emotional behavior (Delinard et al 1981;Beard et al 1993;Han and Kim 2015;Menon et al 2016). For example, iron deficiency in children causes increased anxiety and depression along with social and attention problems (Lozoff et al 2000).…”
mentioning
confidence: 99%